A clinical case of ischemic stroke in a young patient with a previously undescribed nucleotide sequence c.808T > C (p.Tyr270His of the GLBI gene (NM_ 000404.3, GMI-gangliosidosis type 2) in a heterozygous state - N. V. Komissarova; A. A. Malkova; O. P. Potorochina; A. A. Ovchinnikova; P. O. Ivanina; D. O. Bayusheva (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье)
At this stage in the development of medicine, there are difficulties in establishing the etiology of stroke in young patients. There are few significant risk factors from the group of metabolic hereditary diseases in the development of "young" strokes in the literature. This prompts the publication of our observation. Aim: to describe a unique clinical case of "young" ischemic stroke in a 27-year-old woman whose daughter was diagnosed with type 2 gangliosidosis. To determine the cause of the stroke, the patient underwent DNA diagnostics, which showed a previously undescribed nucleotide sequence. A clinical case of ischemic stroke caused by a previously undescribed nucleotide sequence is presented.